Pelanggaran Hak Asasi dalam Rumah Tangga Perspektif Hukum Keluarga Islam dan Kitab Undang-Undang Hukum Positif Indonesia - Alfariszi, Maajid; Ahsan, Khoirul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to analyze violations of human rights within the household from the perspectives of Islamic family law and the Positive Law of Indonesia. The research methodology employed is a descriptive-analytical approach, involving data collection from various sources such as literature, legal documents, and case studies. The findings indicate that violations of human rights within the household often occur in various forms, including physical, psychological, and sexual violence, and neglect. In the context of Islamic family law, principles of justice, equality, and family welfare serve as guidelines for addressing cases of human rights violations within the household. On the other hand, the Positive Law of Indonesia provides a strong legal framework for protecting individual rights within the household, although its implementation may require further improvement. Therefore, collaborative efforts among legal institutions, civil society, and religious organizations are necessary to enhance awareness, protection, and enforcement of human rights within the context of the household.